Softening the body, softening the language, softening the tradition: "Mi paese salvaje" by Ángela Segovia - Alonso González, Mario (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
The present study analyses the creative reception of mystic literature in Ángela Segovia’s Mi paese salvaje. Through the liquid aesthetic of mystic and of this lyric work, I have studied the particular manner in which a poetics of the fragile and of softening has been developed – transcending the textual boundaries to become a way of understanding the world, ourselves and our bodies, a way of apprehending death and life as necessary parts of existence. Besides, I have analyzed how this softening occurs as well within the lyric language and in the mixing of the different literary traditions in Mi paese salvaje.